PERAN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DALAM MENCEGAH BRIDE TRAFFICKING DI INDIA TAHUN 2011-2014 - Darma, Sari Eza; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study of contemporary which discussing about the role of the United Nations Office On Drugs And Crime (UNODC) in Preventing Bride Trafficking in India. Bride Trafficking is not a new phenomenon in India. This practice is known as the Bride Buying in past time. Bride Trafficking is one form of human trafficking that make women and girls (brides) as victims on behalf of marriage and sold from one person to another only as sex objects. Victims generally come from poor families and vulnerable to rape, abuse, social discrimination, physical and psychological violence. Bride Trafficking occurs between regions in India but several victims also come from other countries such as Bangladesh.In this research, the author uses the group behavior analysis level which focused on the role of international organization. This research uses a pluralist perspective in international relations and organizational theory of Clive Archer. UNODC's role in preventing Bride Trafficking in India by 3P program (Prevention, Protection and Prosecution).In effort to prevent Bride Trafficking in India, UNODC faced some obstacles. The lack of public knowledge about the dangers of Bride Trafficking, lack of resource capacity in India and lack of monitoring and evaluation of the Indian government so that the victims of Bride Trafficking increased from year to year.Keywords: Bride Trafficking, Human Trafficking, the United Nations Office On Drugs And Crime (UNODC), Prevention, Protection, Prosecution.